2019
DOI: 10.1155/2019/4164097
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Temperature and Humidity Prediction from Fourier-Statistical Analysis of Hourly Data

Abstract: The temperature readings for all the 365 days and the 24 hours may be fitted through a 3 × 3 matrix (the so-called T-matrix). The mean square deviation between this fit and the actual meteorological measurements is smaller than three degrees Celsius. Four entries of this (nonsymmetric) matrix may be fixed by other means, leaving only five independent components. However, the same method applied to the humidity measurements produces a larger mean square deviation. A strong stochastical connection is found betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Recently, the world has generated electric power from wind turbines, but the airflow control strategy for wind turbines has uncertainty. However, with the developments in meteorological temperature and humidity predictions from Fourier-statistical analysis of hourly data, which guarantees its operation [34][35][36], the temperature readings for all the 365 days and the 24 h may provide a strong stochastical connection to the classic strategy. Likewise, the neural network models were able to perform cold wind control [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the world has generated electric power from wind turbines, but the airflow control strategy for wind turbines has uncertainty. However, with the developments in meteorological temperature and humidity predictions from Fourier-statistical analysis of hourly data, which guarantees its operation [34][35][36], the temperature readings for all the 365 days and the 24 h may provide a strong stochastical connection to the classic strategy. Likewise, the neural network models were able to perform cold wind control [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…As fossil energy reserves continue to shrink and environmental problems become more prominent, countries around the world increasingly favor clean energy sourced from the Earth's cycles. For example, the world has generated electric power from wind turbines with uncertainty on airflow control, most recently, using a classic strategy of Fourier-statistical analysis of hourly data, which guarantees the continuous operation [1][2][3]. Furthermore, suitable neural network models were able to perform predictions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…An example would be monitoring and forecasting climate conditions. Scientific studies have shown that, for opencast agriculture, Fourier analysis of hourly data demonstrates that the atmospheric pressure intervened in the occurrence of rainfall on semi-arid regions [13][14][15][16]. The production management in greenhouse systems demands decision-making over several timescales.…”
mentioning
confidence: 99%